Electrophilic Susceptibility of Graphene Quantum Dots: Hypochlorous versus Hypobromous Acids─Experimental and Theoretical Study - Mizumoto, Guilherme Justiniano [UNESP]; Morgon, Nelson Henrique; de Souza, Aguinaldo Robinson [UNESP]; Ximenes, Valdecir Farias [UNESP] (American Chemical Society (ACS), 2025)
Graphene quantum dots (GQDs) are water-soluble, are biocompatible, and exhibit low toxicity. These properties, along with their adjustable and efficient fluorescent emission, make GQDs valuable for biological applications, particularly as spectroscopic nanosensors. In this context, GQDs have been utilized to detect hypochlorous acid (HOCl). While HOCl is a well-known synthetic disinfectant, it is also naturally produced by the enzyme myeloperoxidase (MPO) in mammals. This heme-peroxidase also catalyzes the production of hypobromous acid (HOBr), a more potent halogenating agent. In our study, we compared the reactivity of HOCl and HOBr with GQDs. By monitoring the fluorescence bleaching of the GQDs, we demonstrated that HOBr is more reactive than HOCl. The increased reactivity was attributed to HOBr’s higher electrophilicity. The electrophilic nature of the reaction was further confirmed by introducing nicotine as a chlorination catalyst. Anisole did not inhibit the electrophilic attack, confirming the high reactivity of GODs with HOBr. The enzyme MPO was used to generate HOBr through oxidation of Br- by H2O2. Thus, the enzymatic activity of MPO could be monitored by GQDs’ fluorescence bleaching, and the efficiency of MPO inhibitors could be evaluated. We applied differential function theory (DFT) methodologies to support our experimental findings, proposing a transition state for the electrophilic attack. Consistent with our experimental results, the energetic barrier for the reaction with HOBr was lower than that for HOCl. Overall, our results indicate the susceptibility of GQDs to electrophilic attacks by hypohalous acids and highlight new opportunities for biological applications.